Optimal Scheduling Strategy for Virtual Power Plant Considering Electricity-Gas-Heat Coupling and Demand Response - Shijie WANG; Tianbo FENG; Ning SUN; Ke HE; Jiawen LI; Cheng YANG; Haoyang CUI (Zhongguo dianli)
The combined heat and power (CHP) units can not meet the maximum heating efficiency and power peak shaving demand in winter at the same time, and there exit problems of insufficient power generation output regulation ability. In view of the above problems, an optimal scheduling strategy for virtual power plant (VPP) is proposed considering electricity-gas-thermal energy coupling and demand response. Firstly, in order to improve the downward peak shaving capacity of CHP units, the P2G equipment and carbon capture technology are introduced to construct a new CHP coupling model. Secondly, in order to improve the operation flexibility of the system, considering the peak-valley time-of-use electricity price and heat price, a comprehensive demand response mechanism is established. And then, in order to reduce the generation cost of the system, the electric and thermal energy storage devices are introduced, and a VPP bi-level optimization model is established with the goal of minimizing the total cost of the system and the operation cost of the electric and thermal energy storage devices. According to the Karush-Kuhn-Tucher ( KKT ) condition of the lower-level optimization model, the bi-level model is transformed into a single level and linearized for solution. The results show that the carbon emissions, operation cost and new energy consumption rate of the proposed method are optimal, which improves the downward peak shaving capacity of the CHP units and meets the low-carbon and economic requirements of the system.